Fruit and vegetable intake is inversely associated with perceived stress across the adult lifespan. Issue 5 (May 2021) - Radavelli-Bagatini, Simone; Blekkenhorst, Lauren C.; Sim, Marc; Prince, Richard L.; Bondonno, Nicola P.; Bondonno, Catherine P.; Woodman, Richard; Anokye, Reindolf; Dimmock, James; Jackson, Ben; Costello, Leesa; Devine, Amanda; et al.
Summary: Background & aims: Poor nutritional habits are linked to higher perceived stress, but the relationship between fruit and vegetable (FV) intake and stress is uncertain. The primary aim of this cross-sectional study was to explore the relationship between FV intake and perceived stress in a population-based cohort of men and women aged ≥25 years from the Australian Diabetes, Obesity and Lifestyle (AusDiab) Study. A secondary aim was to investigate the relationship between serum carotenoids, biomarkers of FV intake, and perceived stress. Methods: In Australian men and women, dietary intake was assessed using a Food Frequency Questionnaire in 1999–2000 (n = 8689). Perceived stress was assessed using a validated Perceived Stress Questionnaire [PSQ index values ranging from 0 (lowest) to 1 (highest)]. Serum carotenoids were measured in a subset of participants (n = 1187) using high-performance liquid chromatography. Multivariable-adjusted linear and logistic regression were performed to investigate the associations between FV intake and perceived stress. Results: Mean age of participants was 47.4 (SD 14.1) years (49.8% females). Participants with the highest intakes of FV had 10% lower PSQ index values than those with the lowest intake [Q4: 0.27 ± 0.004 vs. Q1: 0.30 ± 0.004 (mean ± SE), p = 0.004]. Similar associations were found for fruits and vegetables, analysed separately. In subgroup analyses higher FV intake was associated with lower perceived stress in the middle-aged adults [≥45-<65 years (p = 0.004)], but not in the younger (<45 years) and older participants (≥65 years). Higher FV intake was also significantly associated with lower perceived stress in men (p = 0.009) and women (p = 0.012), separately. Serum carotenoid levels were inversely associated with perceived stress before, but not after adjusting for age and other confounding factors. Conclusion: In Australian adults, higher FV intake was associated with lower perceived stress, particularly in the middle-aged adults. These findings support current recommendations that fruit and vegetables are essential for health and well-being.